CD40 ligation-induced ERK activation leads to enhanced radiosensitivity in cervical carcinoma cells via promoting autophagy - Liu Baocai; Zhang Yadong; Wang Quan; Wang Qian; Wang Zhixin; Feng Li (Acta Biochimica et Biophysica Sinica)
CD40, a member of the tumor necrosis factor (TNF) receptor superfamily, plays an important role not only in the immune system but also in tumor progression. CD40 ligation reportedly promotes autophagy in immune cells. However, the effects of CD40 ligation on autophagy and its mechanism in solid tumor cells are still unclear. In this study, we find that CD40 ligation promotes autophagosome formation and consequently promotes autophagic flux in cervical cancer cells. Mechanistically, this effect relies on ERK contributing to CD40 ligation-induced ATG13 upregulation by p53. Furthermore, we demonstrate that CD40 ligation-induced autophagy increases the radiosensitivity of cervical cancer cells. Taken together, our results provide new evidence for the involvement of the CD40 pathway in autophagy and radiotherapy in cervical cancer cells.